Nilai Etika dan Pengendalian Diri dalam Cerita Kirtimukha pada Ornamen Karang Boma sebagai Landasan Pendidikan Karakter Siswa Hindu - Purnamantha, I Gede Tino; Supadmini, Ni Kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Ethical and moral problems among students, such as bullying and weak self-control, indicate that character education has not been optimally internalized in school learning processes. In Hindu teachings, ethics (śīla) and self-control (dama) constitute the fundamental foundations of character formation based on dharma. These values are not only found in sacred texts but are also symbolically embodied in Balinese local wisdom, particularly in the story of Kirtimukha as represented in the Karang Boma ornament. This study aims to examine the symbolic meaning of the Kirtimukha narrative embodied in the Karang Boma ornament, to analyze the ethical values and principles of self-control contained within the story, and to explain their relevance as a foundation for Hindu students’ character education. This research employs a qualitative approach through library research and symbolic analysis. The findings reveal that the Kirtimukha narrative embodies values of obedience to dharma, restraint of desire and anger, subjugation of ego, and moral responsibility. These values are highly relevant for integration into Hindu religious education to foster students who are disciplined, ethical, religious, and capable of self-regulation in their social and moral lives. Keywords: Kirtimukha; Karang Boma; Hindu ethics; self-control; character education.